1997
DOI: 10.1121/1.418053
|View full text |Cite
|
Sign up to set email alerts
|

A re-examination of risk estimates from the NIOSH Occupational Noise and Hearing Survey (ONHS)

Abstract: This paper describes a new analysis of data from the 1968-72 National Institute for Occupational Safety & Health (NIOSH) Occupational Noise and Hearing Survey (ONHS). The population consisted of 1172 (792 noise-exposed and 380 "controls") predominately white male workers from a cross section of industries within the United States. The analysis focused on how risk estimates vary according to various model assumptions, including shape of the dose-response curve and the amount of noise exposure among low-noise ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 2 publications
3
85
0
3
Order By: Relevance
“…Also, the highest risk is found at the highest levels of exposure. Prince et al (1997) found a small increase in excess risk in workers exposed to 80 -84 dBA versus the < 80 dBA control group; however, these risk estimates are imprecise due to low numbers of workers in the study exposed to noise at these levels.…”
Section: Application Of Us Data To Other Subregionsmentioning
confidence: 82%
See 1 more Smart Citation
“…Also, the highest risk is found at the highest levels of exposure. Prince et al (1997) found a small increase in excess risk in workers exposed to 80 -84 dBA versus the < 80 dBA control group; however, these risk estimates are imprecise due to low numbers of workers in the study exposed to noise at these levels.…”
Section: Application Of Us Data To Other Subregionsmentioning
confidence: 82%
“…Excess risks for hearing loss >25 dBA resulting from moderately high and high noise exposure were taken from an article by Prince et al (1997) based on U.S. data, and adjusted to match the definition of hearing loss used by WHO, i.e., > 41 dBA. Relative risks were estimated from excess risks using data on background hearing loss at given ages taken from England (Davis, 1989).…”
Section: Basic Methodologymentioning
confidence: 99%
“…The notch from occupational noise can occur between 3,000 and 6,000 Hz [ACOM 1989;Osguthorpe and Klein 2001]. However, it is generally accepted that a notch at 4,000 Hz indicates occupational hearing loss [Prince et al 1997]. An individual may have notches at different frequencies in one or both ears [Suter 2002].…”
Section: Noise Sampling Methodsmentioning
confidence: 99%
“…17,18 It is generally accepted that a notch at 4000 Hz indicates occupational hearing loss. 19 On the other hand, some researchers have argued that the notch at 6000 Hz may not be a good marker for occupational hearing loss because it is widely seen in young adults and others with little documented occupational noise exposure. 20 An individual may have notches at different frequencies in one or both ears.…”
Section: Evaluation Criteriamentioning
confidence: 99%